PENGARUH PENAMBAHAN BUBUK BUNGKIL KELAPA TERHADAP PERMEN COKELAT YANG DIHASILKAN - Jumriah Langkong; Rindam Latief; Namira Syaifudin (Jurnal Penelitian dan Pengembangan Agrokompleks, 2018)
Chocolate candy is one of food products favored by children and society. Chocolatecandies was prepared by defatted coconut powder as a filler. Chocolate candy was made simplewith the main ingredients: cocoa butter (350 grams), cocoa powder (8%), refined sugar (28%),lecithin (0.5%), and defatted coconut powder. The treatment were the different amount ofdefatted of coconut powder, namely A1 (22%), A2 (27%), and A3 (32%). The purpose of thisstudy was to get of the amount of defatted coconut powder formulations to be used and todetermine the physical, chemical and acceptabillity (organoleptic) of chocolate candy. Theparameters were stability, fat bloom, water content, and organoleptic tests include color,aroma, taste, and texture. The results showed that the chocolate had good stability, the watercontent ranged from 0.61%-1.37%. The use of defatted coconut powder with levels of 22% toproduce chocolate candy products ware relatively more preferred by panelists on theorganoleptic parameters of color and texture.